Mesothelioma in Two Nondomestic Felids: North American Cougar (Felis concolor) and Cheetah (Acinonyx jubatus). (23rd May 2013) - Whiton, Amanda; Schumacher, Juergen; Evans, Erika E.; Novak, Janelle M.; Crews, Amanda; Ramsay, Edward; Donnell, Robert
Abstract : A 15-year-old male North American cougar ( Felis concolor ) presented with a 2-day history of anorexia, restlessness, and dyspnea. White blood cell count (22.5 × 10 3 cells/ μ L) and absolute segmented neutrophil count (21.09 × 10 3 cells/ μ L) were increased, and BUN (143 mg/dL), creatinine (6.3 mg/dL), and phosphorus (8.5 mg/dL) concentrations indicated chronic renal disease. Thoracic radiographs showed severe pleural and pericardial effusion. During attempts to remove the fluid, cardiac tamponade developed and the cat died. At necropsy, nodular masses decorated the pericardium at the level of the base of the heart. The final microscopic diagnosis was mesothelioma of the pericardium, tunica adventitia of the main pulmonary artery, left auricle epicardium, and left ventricular epicardium. A 15-year-old female cheetah ( Acinonyx jubatus ) was evaluated for acute respiratory distress. The white blood cell count (25.5 × 10 3 cells/ μ L) and absolute segmented neutrophil count (22.19 × 10 3 cells/ μ L) were increased. Radiographically pleural effusion and a cranial thoracic mass were seen. The cheetah was euthanized, and a gross diagnosis of disseminated pleural mesothelioma with thoracic effusion was made. Histologically, pleural mesothelioma was confirmed with local invasion of the lung and pulmonary arterial emboli and infarction. In both cases, a diagnosis of mesothelioma was made based on cellular morphology, microscopic architecture, and neoplastic cell coexpression of cytokeratin and vimentin.